2019
DOI: 10.1007/s11676-019-00994-x
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale habitat differentiation shapes the composition, structure and aboveground biomass but not species richness of a tropical Atlantic forest

Abstract: Evaluating the influences of fine-scale habitat heterogeneity on the composition, diversity, structure and functioning of forests is critical to understand how tropical forests will respond to climate change and devise forest management strategies that will enhance biodiversity conservation and aboveground biomass stock. Here, we hypothesized that topographic and soil factors determine fine-scale habitat differentiation, which in turn shape community composition, species richness, structure and aboveground bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 51 publications
1
19
0
3
Order By: Relevance
“…Our results showed that SAD attributes varied with either topographical factors or soil nutrients, whereas SR only exhibited significant variations along soil nutrient gradients. The resulting weak SR–topography relationship is consistent with the recent finding in a tropical forest ( Rodrigues et al, 2020 ). We further discovered that soil nutrients accounted for more variations in species dominance, rarity, and richness than topographical factors, reflecting a relatively greater importance of soil nutrients in governing local diversity patterns.…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed that SAD attributes varied with either topographical factors or soil nutrients, whereas SR only exhibited significant variations along soil nutrient gradients. The resulting weak SR–topography relationship is consistent with the recent finding in a tropical forest ( Rodrigues et al, 2020 ). We further discovered that soil nutrients accounted for more variations in species dominance, rarity, and richness than topographical factors, reflecting a relatively greater importance of soil nutrients in governing local diversity patterns.…”
Section: Discussionsupporting
confidence: 91%
“…Rarefaction was estimated as the mean of 100 replicate bootstrapping runs to estimate 95% confidence intervals (e.g. Campos et al 2018;Rodrigues et al 2019;2019b). Whenever the 95% confidence intervals did not overlap, species numbers differed significantly at P < 0.05 (Colwell et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The total AGB per plot was the sum of the AGBs of all trees with a DBH ≥ 10 cm, which was then converted into megagrams per hectare (Mg ha − 1 ) (Rodrigues et al 2019a(Rodrigues et al , 2019b. Species-level biomass was calculated as the sum of the biomass of all stems from a given species.…”
Section: Estimation Of Aboveground Carbonmentioning
confidence: 99%
“…At regional scale, precipitation, temperature and elevation are the main factors affecting the vegetation growth and distribution ( Siefert et al., 2012 ). However, in the same study area, there is no difference in the precipitation and temperature, thereby micro-environmental factors, such as soil physicochemical and biological properties, slope and its aspect may be the key factors affecting the plant composition ( Pennington et al., 2017 ; Nie et al., 2019 ; Rodrigues et al., 2019 ). Before the forest transformation, soil properties were not significantly different in the P. massoniana and C. lanceolatam pure plantations.…”
Section: Discussionmentioning
confidence: 99%